Apophatic and Anthropomorphic Visions of God in Philo of Alexandria - Mackie, Scott D. (Verbum Vitae, 2023)
Despite his core theological convictions that God is incorporeal, formless, invisible, and unchangeable, in some of his most carefully crafted visio Dei texts Philo portrays God “changing shape” and temporarily adopting a human form. However, these are only “seeming appearances” and actually involve God projecting a human-shaped “impression,” or “appearance” (φαντασία) from his shapeless, immaterial being. By accommodating the overwhelming reality of God’s being to the perceptual and conceptual limitations of the human percipient, these docetic theophanies allow humans to more confidently relate to the deity, while at the same time preserving God’s absolute transcendence and apophatic otherness.